Alteration of Ca/P Ratio and Hydroxyapatite Stability in Human Teeth Exposed to Lead: An In Vitro Experimental Study - Iskandar, Iskandar; Essy Dwi Damayanthi; Gusti Muhammad Perdana Putera; Hapsari Lintang Sekartaji; Eko Suhartono (Universitas Wijaya Kusuma Surabaya, 2026)
Background: Lead (Pb) contamination in aquatic environments has been associated with increased dental health problems in exposed populations. One proposed mechanism underlying this association is the disruption of dental hydroxyapatite (HAp) stability through calcium (Ca) substitution and phosphate (P) degradation, which may alter the Ca/P ratio and mineral integrity. Therefore, this study was conducted to experimentally evaluate the impact of Pb exposure on Ca, P, and Ca/P ratio in human teeth under in vitro conditions. Objective: this study aimed to evaluate the effect of Pb exposure on changes in Ca, P, and Ca/P ratio, as well as the degradation kinetics of HAp in vitro. Methods: This true experimental study employed a completely randomized factorial design. Extracted human teeth were immersed in PbSO₄ solutions at concentrations of 0.01, 0.1, and 1 ppm for 30, 60, and 90 minutes. Ca and P levels were measured, and the Ca/P ratio was calculated. Degradation kinetics were analysed using linear regression to determine reaction order and rate constants. Result: Pb exposure resulted in a consistent reduction of the Ca/P ratio across all concentrations and exposure durations, with values below the stoichiometric hydroxyapatite ratio (1.67), indicating increased mineral instability. Both Ca and P degradation followed zero-order reaction kinetics, with higher degradation rate constants observed at 0.01 and 1 ppm. Conclusion: these findings provide experimental evidence that Pb exposure can destabilize dental hydroxyapatite by accelerating Ca and P degradation, thereby potentially increasing susceptibility to mineral loss.